EQUALITY OF SYNONYMS IN TRANSLATIONS METHODS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2021)
In the context of this article, we will try to consider methods and techniques based on the objective laws of achieving adequacy using the translation of stylistic synonyms. One of the key concepts in translation studies is equivalence. Opinions about equivalence have changed over the years. In translation, the problem of equivalence has attracted the attention of many scholars.